PERLINDUNGAN KONSUMEN PADA TRANSAKSI E-COMMERCE DALAM PERSPEKTIF AZAS KEBEBASAN BERKONTRAK - Siahaan, Sahala Parlindungan Siahaan; Hulman Panjaitan; Hendri Jayadi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Another impact of the development of information technology and the internet is the rise of online trading or what is commonly referred to as an electronic commerce (E-commerce), which is a business or trading activity that utilizes computer or internet networks, involving buyers or consumers as well as manufacturing service providers. and intermediary traders as well as covering the whole spectrum of commercial activities. The research methodology used by the author is normative juridical which is descriptive in nature, to find out how the protection and legal standing of the parties in e-commerce transactions in the perspective of the principle of freedom of contract. In order to guarantee legal certainty for consumer protection, it is necessary to regulate the online transaction process. Because negatively, the spectacular development of electronic transactions can be explained by the fact that such transactions give rise to unequal bargaining power between business actors and consumers.